2022
DOI: 10.3390/ijerph19106263
|View full text |Cite
|
Sign up to set email alerts
|

Experiences, Emotions, and Health Consequences among COVID-19 Survivors after Intensive Care Unit Hospitalization

Abstract: Literature suggested that COVID-19 patients experienced hospitalization as a physically and psychologically stressful event, with the risk to develop post-traumatic stress symptoms. The study aimed to understand psychological experiences of COVID-19 survivors with severe complications during and after ICU hospitalization, and any relevant health consequences. From October 2020 to January 2021, a qualitative study was conducted in Italy via semi-structured interviews by phone or video call addressed to COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Older adults have been disproportionally affected across the various waves ( Hadjistavropoulos & Asmundson, 2022 ) and have been subjected to multiple stressors. They have more chronic diseases and risk factors for complications related to COVID-19 (e.g., hypertension, diabetes; Piras et al, 2022 ) and it is more difficult for them to access to health services ( Lebrasseur et al, 2021 ). Based on patients’ age and their prognostic, triage policies have been developed in various countries (e.g., Italy, USA), to facilitate decision-making in case of lack of resources for critical cares (e.g., use of ventilators; see Antommaria et al 2020 ; White & Lo 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Older adults have been disproportionally affected across the various waves ( Hadjistavropoulos & Asmundson, 2022 ) and have been subjected to multiple stressors. They have more chronic diseases and risk factors for complications related to COVID-19 (e.g., hypertension, diabetes; Piras et al, 2022 ) and it is more difficult for them to access to health services ( Lebrasseur et al, 2021 ). Based on patients’ age and their prognostic, triage policies have been developed in various countries (e.g., Italy, USA), to facilitate decision-making in case of lack of resources for critical cares (e.g., use of ventilators; see Antommaria et al 2020 ; White & Lo 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study helps understand the clinical course of infection, characteristics of hospitalized COVID-19 patients, and hospital-resource utilization associated with severe COVID-19 diseases over time, with implications for how physicians monitor admitted patients for increases in severity during hospital stay and inform resource planning and triage efforts (such as for ventilators and medications). Further, recognizing that past studies [ 21 , 22 ] have found associations with ICU admission and feelings of stress, anxiety, isolation, and depression, both during hospital stay and after discharge, findings offer an opportunity to improve communication with hospitalized patients to reduce both physical and psychological health burden associated with COVID-19 hospitalization. Future studies may further evaluate predictors of population characteristics for severe COVID-19 outcomes, including via analytical statistics comparing patients admitted for COVID-19 infection with the general patient population.…”
Section: Discussionmentioning
confidence: 94%
“…The same result is found regarding the perceived quality of care for which nurses’ attention to patient needs appears to be crucial. This can probably be explained by the fact that, during hospitalization, nurses have more opportunities than physicians to build a relationship with patients, and they feel free and safe to ask questions and express their needs [ 38 , 39 ]. A literature review [ 40 ] reports some factors that contribute to increasing trust relationships between nurses and patients.…”
Section: Discussionmentioning
confidence: 99%